COVID‐19 in solid organ transplant recipients: A national cohort study from Sweden. Issue 8 (6th May 2021) - Søfteland, John M.; Friman, Gustav; von Zur‐Mühlen, Bengt; Ericzon, Bo‐Göran; Wallquist, Carin; Karason, Kristjan; Friman, Vanda; Ekelund, Jan; Felldin, Marie; Magnusson, Jesper; Haugen Löfman, Ida; Schult, Andreas; et al.
Abstract : Solid organ transplant (SOT) recipients run a high risk for adverse outcomes from COVID‐19, with reported mortality around 19%. We retrospectively reviewed all known Swedish SOT recipients with RT‐PCR confirmed COVID‐19 between March 1 and November 20, 2020 and analyzed patient characteristics, management, and outcome. We identified 230 patients with a median age of 54.0 years (13.2), who were predominantly male (64%). Most patients were hospitalized (64%), but 36% remained outpatients. Age >50 and male sex were among predictors of transition from outpatient to inpatient status. National early warning Score 2 (NEWS2) at presentation was higher in non‐survivors. Thirty‐day all‐cause mortality was 9.6% (15.0% for inpatients), increased with age and BMI, and was higher in men. Renal function decreased during COVID‐19 but recovered in most patients. SARS‐CoV‐2 antibodies were identified in 78% of patients at 1–2 months post‐infection. Nucleocapsid‐specific antibodies decreased to 38% after 6–7 months, while spike‐specific antibody responses were more durable. Seroprevalence in 559 asymptomatic patients was 1.4%. Many patients can be managed on an outpatient basis aided by risk stratification with age, sex, and NEWS2 score. Factors associated with adverse outcomes include older age, male sex, greater BMI, and a higher NEWS2 score. Abstract : A retrospective national cohort study reports that Swedish solid organ transplant recipients with COVID‐19 had 30‐day all‐cause mortality of 9.6%, largely recovered renal function, and, at 6 months after infection, stable levels of anti‐spike SARS‐CoV‐2 antibodies.